The Evolution of Business Intelligence Tools in Corporate Financial Management - Rajmohan, Kaushik Uma (AG Volumes, 2024)
In the corporate world, investors and founders place a high value on "financial stability, and business intelligence (BI)" is a key instrument for greatly boosting this stability. The main goal of financial management is to raise money for the business at a minimal cost and use that money to generate enormous profits. In this article review the various literature’s study on business intelligence tools in corporate financial management. It concluded that the evolution of business intelligence (BI) tools has revolutionized corporate financial management by enhancing decision-making, optimizing operations, and mitigating risks. These tools empower organizations with advanced data analytics, enabling strategic financial planning and resource efficiency. By identifying and forecasting financial risks, BI ensures stability and sustainability in business practices. Finance departments leverage BI to correlate financial outcomes with business activities, aligning strategies with corporate objectives. Technologies like OLAP and data mining facilitate intelligent decision-making in complex financial environments. As businesses become increasingly data-driven, BI tools serve as essential assets, fostering growth, competitiveness, and long-term success in an ever-evolving financial landscape.